Towards realising the benefits of citizen participation in environmental monitoring: a case study in an Eastern Cape natural resource management programme - Mtati, Nosiseko (Rhodes University, Faculty of Education, Department of Education, 2020)
The Tsitsa Project focusses on land use management and rural livelihoods in the Tsitsa River catchment in the Eastern Cape Province of South Africa. It is funded by the Department of Environmental Affairs and the environmental monitoring initiative is implemented by Rhodes University, where I am employed as the catchment coordinator. This study explores the environmental monitoring initiative within the bigger Tsitsa Project. Community members in the catchment monitor sediment transportation in the Tsitsa River and its tributaries, which originally became of interest because it is proposed that a dam (Ntabelanga Dam) be established here. This study aims to understand citizen environmental monitoring in the Tsitsa Project; what the project managers regarded as benefits; and how the monitors themselves perceived benefits of participating as monitors. A realist approach was followed, in order to understand the connections between the context and the mechanisms in the project, and how these combined to result in the outcomes observed. Realist research emphasises the importance of context in shaping outcomes such as the achieved benefits of citizen monitoring. Data was collected using a case study method, where each individual monitor and their particular context, was regarded as a case. Semistructured interviews were conducted with 17 monitors and five Tsitsa Project staff; this was supported by field notes and the reviewing of project documents including field reports. The realist analysis looked at the context of the monitors in general and the mechanisms applied by the project in recruiting, training and managing the monitors. A second layer of mechanisms was identified as those responses from the monitors to what the project was introducing to them. Outcomes were both positive and negative, including how long monitors remained in the initiative, what benefits they derived from the process, and what potential benefits they did not achieve. This included lost opportunities to provide recognition for skills and experience gained. Recommendations are made regarding the recruitment, training and management of monitors, to optimise benefits for the monitors, the host institution and the initiative's staff. The study is significant because of its particular yet representative characteristics and it will assist both the Tsitsa Project, which aims to expand its citizen environmental monitoring initiative, as well as wider Natural Resource Management Programmes in South Africa. It is also hoped that it will contribute to the literature on environmental monitoring as a little researched form of citizen science globally.
Keywords: Tsitsa Project; Rural development projects -- South Africa -- Eastern Cape; Environmental monitoring -- South Africa -- Tsitsa River; Environmental monitoring -- Citizen participation -- South Africa -- Tsitsa River; Water supply, Agricultural -- South Africa -- Tsitsa River; Environmental education -- South Africa